Kurz & Knapp Zur Mediengeschichte kleiner Formen vom 17. Jahrhundert bis zur Gegenwart - Gamper, Michael; Mayer, Ruth (Edition Kulturwissenschaft, 2018)
Tweets, text messages, Facebook status updates, or microblog entries: the process of announcing news and sharing knowledge seems to be getting shorter and shorter. This volume relates the current trend of abbreviation to its antecedents, showing that the use of brevity existed long before the digital age. The career of the short form is closely connected to the cultural achievements of the 17th century, and skyrocketed in the run up to the formation of professional media networks in the 19th century. Since then, anecdotes, case studies, brief messages, the miscellaneous, headlines, and tidbits from around the world have formed essential elements of the organization and communication of modern forms of knowledge.